2016
DOI: 10.2474/trol.11.661
|View full text |Cite
|
Sign up to set email alerts
|

Development of a High-Power Two-Roller Traction Tester and Measurement of Traction Curves

Abstract: Measuring and estimating the traction coefficient is necessary to improve transmitting efficiency and design compact, lightweight toroidal continuously variable transmissions (T-CVTs). However, few attempts have been made to measure and estimate the traction coefficient of T-CVTs under practical usage conditions, and the design of T-CVTs has used extrapolated values from traction coefficients measured under low-power conditions. Therefore, we developed a high-power two-roller traction tester to clarify variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A large number of studies [9][10][11][12] have shown that spin losses affect the traction performance of t-CVT significantly. Therefore, decreasing the spin losses can improve the reliability and fatigue life [13] , increase the power density and torque capacity [7,14] , and greatly improve the traction efficiency of traction CVT [15][16][17] .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies [9][10][11][12] have shown that spin losses affect the traction performance of t-CVT significantly. Therefore, decreasing the spin losses can improve the reliability and fatigue life [13] , increase the power density and torque capacity [7,14] , and greatly improve the traction efficiency of traction CVT [15][16][17] .…”
Section: Figurementioning
confidence: 99%
“…The oil film is created in the contact ellipse between drive component and driven component, and the oil film can become highly viscous (known as elastohydrodynamic state) under the high normal force F 𝑁 to ensure the transmitting of a tangential force, which is also called traction force F 𝑇 . Generally, the traction force F 𝑇 can be calculated approximatively by the equation F 𝑇 = πœ‡F 𝑁 , where the traction coefficient πœ‡ is determined by the rheological characteristics of given oil [6,7] .…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies [9][10][11][12] have shown that spin losses affect the traction performance of t-CVT significantly. Therefore, decreasing the spin losses can improve the reliability and fatigue life [13] , increase the power density and torque capacity [7,14] , and greatly improve the traction efficiency of traction CVT [15][16][17] .…”
Section: Figurementioning
confidence: 99%
“…The oil film is created in the contact ellipse between drive component and driven component, and the oil film can become highly viscous (known as elastohydrodynamic state) under the high normal force F to ensure the transmitting of a tangential force, which is also called traction force F . Generally, the traction force F can be calculated approximatively by the equation F = F , where the traction coefficient is determined by the rheological characteristics of given oil [6,7] .…”
Section: Introductionmentioning
confidence: 99%